2019
DOI: 10.1007/s11089-019-00870-9
|View full text |Cite
|
Sign up to set email alerts
|

Dignity as Wisdom at the End of Life: Sacrifice as Value Emerging from a Qualitative Analysis of Generativity Documents

Abstract: End of life and palliative care are viewed in chaplaincy as an important time when spiritual support is considered highly beneficial. Dignity therapy is an important care strategy in this field. This article lends support to the Chochinov protocol using Schwartz's matrix of values. Five dignity therapy Bgenerativity documents^prepared for terminally ill patients using interpretative phenomenological analysis were analyzed using qualitative thematic analysis. The results showed the role of values in the constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In our study, all participants reported autobiographical themes of great depth and relevance, most of which were previously observed by Chochinov et al [ 6 ], namely, periods of passage, often marked by rituals (e.g., marriages, bereavement), life lessons learned, expressions of remorse, hope, and dreams, requests for forgiveness, challenges that have been overcome, declarations of love for family and friends, and personal development in the context of family life. The latter theme was prevalent in all the texts because most important relationships were experienced within this context, and it encapsulated the greatest number of values [ 30 , 50 , 51 ]. This result confirms the importance of expressing one’s values at the end of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all participants reported autobiographical themes of great depth and relevance, most of which were previously observed by Chochinov et al [ 6 ], namely, periods of passage, often marked by rituals (e.g., marriages, bereavement), life lessons learned, expressions of remorse, hope, and dreams, requests for forgiveness, challenges that have been overcome, declarations of love for family and friends, and personal development in the context of family life. The latter theme was prevalent in all the texts because most important relationships were experienced within this context, and it encapsulated the greatest number of values [ 30 , 50 , 51 ]. This result confirms the importance of expressing one’s values at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on generativity documents highlighted the importance of individual values. In particular, it showed how the values that patients considered to be the most important during their lives served as fundamental pivots in their DT narratives [ 30 ]. Based on Schwartz’s intercultural model of values [ 31 , 32 ], which describes the principles guiding people’s behavior as desirable and trans-situational, this study considers dignity as a function of those values that participants cherished over the course of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown how photographs facilitate recollection and allow for a better structuring of the narratives within the Dignity Therapy intervention [ 24 , 62 , 63 ]. Studies indicate how using photographs as therapeutic tools open up ways to recreate the life stories [ 64 ] and engage in the process of meaning making after loss [ 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate how using photographs as therapeutic tools open up ways to recreate the life stories [ 64 ] and engage in the process of meaning making after loss [ 65 , 66 ]. The visual stimuli of the photographs can elicit themes that cannot be expressed by words alone, such as emotions, embodied expressions and muted or sensitive aspects of personal experience [ 62 , 63 ]. Moreover, the photographs, and the connections between them, can be presented in the photocollage as a visual generative document [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a large number of papers using quantitative methods to assess DT's efficacy, across several psychosocial outcomes, qualitative descriptions of themes emerging within generativity documents are still lacking (Goddard et al, 2013; Dose and Rhudy, 2018; Testoni et al, 2019). The latter provides opportunities to explore further and better understand the perspectives of people regarding their end-of-life experience (Johnston et al, 2015; Dose and Rhudy, 2018).…”
Section: Introductionmentioning
confidence: 99%